Study of lightning flashes in Malaysia with attention to their interaction with electrical systems [electronic resource] - 419402 Nor Hayati Abu Bakar; Fakulti Kejuruteraan Elektrik (2007)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2007